Effects of Salvia officinalis L. (common sage) leaves tea on insulin resistance, lipid profile, and oxidative stress in rats with polycystic ovary: An experimental study - Mahnaz Ghowsi; Namdar Yousofvand; Saman Moradi (Mashhad University of Medical Sciences, 2020)
Objective: Oxidative stress conditions and metabolic complications are common among polycystic ovary syndrome (PCOS) patients. There are various reports about hypoglycemic and antioxidant effects of Salvia officinalis L. (common sage). This study evaluated the possible medicinal effects of sage tea drinking on oxidative status, lipid profile, and insulin resistance in rats with testosterone-induced PCOS. Materials and Methods: Eighteen immature female Wistar rats (21-day old) were divided into 3 groups: 1) The Control group (n=6) that received no treatment. 2) The PCOS group (n=6) that received testosterone enanthate 10 mg/kg BW for 35 days subcutaneously. (3) The PCOS -sage tea group (n=6) to which after induction of PCOS by injection of testosterone enanthate, the sage tea was administered as a replacement of water for 14 days. The beverages were refreshed every day. The serum levels of total antioxidant capacity (TAC), malondialdehyde (MDA), glucose, insulin, HDL-C, total cholesterol, LDL-C, VLDL-C, total triglycerides, and atherogenic index were measured. Results: Sage tea consumption increased serum TAC and decreased serum HDL-C, glucose, total cholesterol, LDL-C, and atherogenic index levels but it did not change the levels of MDA, insulin, total triglycerides, and VLDL-C. Conclusion: Results suggested that sage tea consumption may influence the oxidative status and reduce the blood glucose and atherogenic index and may have cardiovascular protective effects in PCOS women.